Communication, technology and ageing: elderly, senior citizen groups and interaction process in the information age Comunicação, tecnologia e envelhecimento: idosos, grupos de terceira idade e processo de interação na era da informação - Adriano Pasqualotti; Dante Augusto Couto Barone; Johannes Doll (Universidade de São Paulo, 2012)
A computational environment will only change the nature of interactionist activity if the changes that are occurring in methods of communication are looked at, as this should favor cooperative work. In order to develop tools that provide opportunity for building knowledge by means of interaction, it is necessary to be aware of biopsychosocial aspects and understand the liberating potential of the communicative processes that are established when individuals interact while mediated through technology. Beginning with a sociohistorical conception of social interaction, we seek to fill a research space in terms of communicative action and the meaning of social representations regarding communication and information technologies. We analyze the triad of communication, technology and ageing, questions are examined that involve elderly people in a biopsychosocial context. We seek to identify symbolic representations in relation to the technologies and analyze the triggered feelings and the meanings of these experiences encountered with the use of these mechanisms. The processes of appropriation are analyzed along with the meaning of technologies with a group of elderly citizens from the city of Passo Fundo - RS, enrolled in informatics workshops. The research is made up of a cross sectional study descriptive nature and population. To analyze relations among the researched variables, applied analysis of variance, chi squared test, factorial analysis and conglomerate analysis. The data was analyzed on a significance level of 5% (p ≤ 0.05). The results indicate that the elderly participate in the workshops especially with the purpose of maximizing the processes of coexistence. Um ambiente computacional mudará a natureza da atividade interacionista se contemplar as mudanças que estão ocorrendo nos métodos de comunicação, pois deve favorecer o trabalho cooperativo. Para desenvolver ferramentas que viabilizem a construção do conhecimento por meio da interação é preciso conhecer os aspectos biopsicossociais e entender o potencial libertador dos processos comunicativos que se estabelecem quando os sujeitos interagem mediados pela tecnologia. Partindo de uma concepção sócio-histórica de interação social, procuramos preencher um espaço de pesquisa em relação à ação comunicativa e à significação das representações sociais sobre as tecnologias de comunicação e informação. Analisamos a tríade comunicação, tecnologia e envelhecimento, objetos de natureza distinta que advêm quando se ponderam questões que envolvem pessoas idosas num contexto biopsicossocial. Buscamos conhecer as representações simbólicas em relação às tecnologias e analisar os sentimentos desencadeados e o significado das experiências vividas com o uso desses dispositivos. Analisamos os processos de apropriação e significação das tecnologias com um grupo de idosos matriculados em oficias de informática do município de Passo Fundo - RS. A pesquisa é um estudo transversal de cunho analítico e populacional. Para analisar os dados utilizamos análise de variância, teste qui-quadrado, análise fatorial e análise de conglomerado em um nível de significância de 5% (p ≤ 0,05). Os resultados revelam que os idosos participam das oficinas com a finalidade de maximizar os processos de convívio, resultado que ratifica a importância dos programas de educação permanentes oferecidos pelas universidades abertas.